Endophytic bacteria isolated from stems and roots of Acrostichum aureum Linn. potential for hydrolytic enzyme and α-amylase inhibitor - Linda, Tetty Marta; Defani, Syafiqah Amirah; Berliansyah, Azizul; Febriarti, Bernadeta Leni; Zul, Delita (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Endophytic bacteria live symbiotically in plant tissues but do not hurt plants. Endophytic bacteria are widely used in the industrial sector as enzyme producers. This study aims to examine the potential of endophytic bacteria from the stems and roots of sea fern (Acrostichum aureum L.) as producers of hydrolytic enzymes and to determine their potential as α-amylase inhibitors. Macroscopic and biochemical tests characterized endophytic bacterial isolates. Hydrolytic enzyme activity test consisted of cellulase, lipase, and laccase enzyme. Isolates that were able to hydrolyze were tested for antidiabetic potential by α-amylase inhibitor test. A total of 24 bacterial isolates were selected for their ability to produce cellulase, lipase, and laccase. The results obtained 24 isolates of endophytic bacteria showed that as much as 33% of stem isolates and 52% of root isolates were able to produce hydrolytic enzymes. The α-amylase inhibition test results of the three endophytic bacteria tested were isolates A.T 2 (17%) and A.A 3 (8%) on 1% starch substrate, and A.T 2 (36%) on 2% starch substrate with a spectrophotometer at a wavelength of 540 nm. Endophytic bacteria isolated from the stems and roots of sea ferns can be developed as an alternative base material for herbal medicines for antidiabetics.